Determination of flow parameters for pipe flows by the radiotracer techniques - Tugrul, B.; Kara, N. (Springer Science and Business Media LLC, 1994)
In this study, the measurement of flow rate in pipes is obtained in the laboratory by two different radiotracing techniques, the “peak to peak” method and the “radiotracer balance” method. Sodium-24 has been used as the radiotracer and irradiation has been done in the I.T.U. TRIOA Mark-II Reactor. The peak to peak method is also applied with only one detector. The sensitivity of the methods are obtained for different conditions. Experimental results which are taken for the techniques are compared to each other and are evaluated with the flow parameters.